Leukemic gingival enlargement- A case report and review - Eyakshara, S; Manoharan, GV Murali Gopika (Indian Journal of Case Reports, 2024)
Oral signs are an early indicator for a variety of systemic diseases. Gingival enlargement can be due to local factors, certain medications, hormonal changes, and malignant diseases. Leukemia is a malignancy characterized by the proliferation of abnormal white blood cells within the bone marrow; oral changes may be the first and only presenting feature in these patients, making it imperative for dental surgeons to make accurate diagnosis and timely referral to prevent a fatal situation. This article aims to discuss a case of acute myeloid leukemia (AML) that came with the chief complaint of swollen gums for 2-month duration. The case was provisionally diagnosed as a leukemic gingival enlargement on the basis of oral manifestation and lymph node examination. Accurate diagnosis and early initiation of chemotherapy for leukemic gingival enlargement can improve the prognosis of the patient and also helps in avoiding complications. Around 50–80% of patients with AML achieve complete remission, more often in children and patients under the age of 60. This paper aims at emphasizing the importance of thorough oral examination and careful investigations to identify the underlying life-threatening condition.